Occurrence of hydrocarbon degrading bacteria in soil in Kukawa, Borno State - Allamin, IA; Ijah, UJJ; Ismail, HY; Riskuwa, ML (International Journal of Environment, 2014)
Soil samples were collected from five sites covering petroleum exploration station in Kukawa, Kukawa Local Government Area of Borno State, Nigeria between October, 2012 and February, 2013 at two different depths (0-10cm and 10-20cm) to enumerate and identify hydrocarbon degrading bacteria in the soil. Total aerobic heterotrophic bacteria (TAHB) were enumerated on Nutrient agar (NA), and Hydrocarbon utilizing bacteria (HUB) enumerated on Oil agar (OA). The bacterial isolates were identified using morphological and biochemical tests. It was observed that the microorganisms (TAHB, and HUB) were more densely populated at 10cm depth. (TAHB: 5.3×108 - 11.4×108cfu/g, and HUB: 2.4×105 - 5.3×105 cfu/g, than at 20 cm depth (TAHB: 3.0×108 - 5.7×108 cfu/g, and HUB: 2.1×105 - 4.8×105 cfu/g). The HUB was identified as species of Bacillus, Pseudomonas, Klebsiella, Lactobacillus, Micrococcus, Corynebacterium, and Actinomyces. Bacillus, and Pseudomonas species were more constantly isolated than other isolates and they constitute 100% of total bacterial isolates. The potential of hydrocarbon utilizing bacteria isolated to degrade hydrocarbon was studied. Nineteen (19) bacterial species was screened, Bacillus subtilis, Pseudomonas aeruginosa, Bacillus cereus, Klebsiella pneumoniae, Micrococcus leteus,and Lactobacillus casei, utilized and degrade crude oil at considerably high rates after 21 days of incubation. The degradation efficiency was confirmed by GC-MS analysis, which indicated that the bacterial isolates utilized most of the crude oil components particularly straight chain alkanes and cycloalkanes DOI: http://dx.doi.org/10.3126/ije.v3i2.10503 International Journal of the Environment Vol.3(2) 2014: 36-47